Results of a new “mirror tuck technique” for fixation of lacrimal bypass tube in conjunctivodacryocystorhinostomy - Goel, Ruchi (Indian J Ophthalmol, 2017)
CONTEXT: Conjunctivodacryocystorhinostomy (CDCR) is the procedure of choice for proximal canalicular blocks. However, the complications of tube migration and extrusion limit its widespread practice. AIM: The aim of this study is to evaluate the efficacy and complications of the new “mirror tuck technique” for fixation of lacrimal bypass glass tube without holes in proximal canalicular blocks in laser CDCR. MATERIALS AND METHODS: A prospective interventional study was conducted in forty consecutive eyes of adult patients, undergoing 980 nm diode laser CDCR for proximal canalicular blocks. After creating the tract under endoscopic guidance, the collar of the glass tube was fixed to the conjunctiva with 6-0 prolene suture by “mirror tuck technique.” Success was defined as the absence of extrusion of tube with patent tract and relief in epiphora at 1 year of follow-up. RESULTS: Both anatomical and functional success was achieved in 39 (97.5%) cases. Tube displacement occurred in one patient suffering from allergic conjunctivitis in which the tube had to be removed. A temporary heaviness was reported by 5 (12.5%) patients till about 2 weeks. Conjunctival overgrowth over the tube occurred in 1 (2.5%) eye at 5 months which was excised and treated with application of 0.02% mitomycin C with no subsequent recurrence. There were no cases of suture abscess or suture intolerance warranting tube removal. CONCLUSION: “Mirror tuck technique” is an effective method for tube fixation (for tube without holes) in CDCR. However, it is important to position the conjunctival opening so as to leave sufficient space for passage of sutures for anchorage medially.